Tinjauan Hukum Islam Terhadap Praktik Jual Beli Tanah Pembatalan Sepihak Dengan Sistem Uang Muka - Saipudin; Evin Saimah (STAI Al-Ma'arif Way Kanan, 2021)
In general, people refer to trading as buying and selling. There are several buying and selling systems that occur in the community, one of which is the practice of buying and selling land with a down payment system that occurs in the Sriwijaya village. In the sale and purchase of land with a down payment system of course accompanied by an agreement on stamp duty and witnesses. The down payment given by the prospective buyer is intended as a sign of a land sale and purchase transaction and the sincerity of the prospective buyer to buy the land that has been offered by the prospective seller. Sale and purchase is an agreement to exchange objects or goods that have a value that is carried out voluntarily between the two parties with the terms and conditions justified by sharia and agreed upon. The sale and purchase of an advance (advance payment) is an amount of money that is paid in advance as a sign of the purchase of an item. In this sale, there is a contract and khiyar (right of cancellation) in the sale and purchase carried out by both parties. The research used to examine the title of this thesis, the author uses qualitative research. Sources of data in this study include primary and secondary data sources, as well as in data collection include, observation, documentation and interviews. Based on research conducted, that in the practice of buying and selling land with a down payment system, namely where the seller offers a sale and purchase but with an initial payment of 30% of the original price. For the system of buying and selling land with this down payment system, they do not accept losses from one another, with this they both benefit because they get justice and the benefits can be felt by both parties. The down payment system in the Sriwijaya village is allowed because no party is harmed by the sale and purchase transaction of land with the down payment system